2018
DOI: 10.1002/jia2.25168
|View full text |Cite
|
Sign up to set email alerts
|

HIV viral suppression and longevity among a cohort of children initiating antiretroviral therapy in Eastern Cape, South Africa

Abstract: IntroductionThere are limited data on viral suppression (VS) in children with HIV receiving antiretroviral therapy (ART) in routine care in low‐resource settings. We examined VS in a cohort of children initiating ART in routine HIV care in Eastern Cape Province, South Africa.MethodsThe Pediatric Enhanced Surveillance Study enrolled HIV‐infected ART eligibility children zero to twelve years at five health facilities from 2012 to 2014. All children received routine HIV care and treatment services and attended qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
3
17
3
Order By: Relevance
“…Even though a high proportion of children initially achieved virological suppression, a substantial proportion (38.3%) subsequently registered at least one pVL ≥ 150 copies per mL, a rate that is similar to a study from South Africa [35]. Those who were classified as being WHO clinical stage 4 had an increased hazard of virologic rebound.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Even though a high proportion of children initially achieved virological suppression, a substantial proportion (38.3%) subsequently registered at least one pVL ≥ 150 copies per mL, a rate that is similar to a study from South Africa [35]. Those who were classified as being WHO clinical stage 4 had an increased hazard of virologic rebound.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, in Ethiopia, there is no disaggregated national pediatric data on the rate of sustained virological suppression among HIV infected children who initiated cART (that is, the statistic represented by the third "90" of the UNAIDS 90-90-90 goal) [5]. Only an aggregate estimate of 86% virological suppression in 2016 has been reported, which is higher than the ESA regional average of 52% [33][34][35]. The current study revealed high initial rates of virological suppression -85.5% of participants achieved pVL <150 copies/mL at some point during study follow up -a rate that is comparable to reports by other studies [8,9,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…While children and young people's access to antiretroviral therapy (ART) has increased dramatically over the past decade, ART adherence and viral suppression remain challenges, especially among highly vulnerable populations in lower-and middle-income countries [1][2][3][4][5][6]. Nondisclosure and lack of routine have been identified as contributing to poor medication adherence and retention in care.…”
Section: Introductionmentioning
confidence: 99%
“…A recent South African study that initiated very early ART reported just over 50% with HIV RNA < 400 copies/mL at 6 months, and > 10% mortality [ 34 ]. Similarly, in several earlier pediatric cohorts in Johannesburg, only 25%–49% achieved 6-month viral suppression to < 50 copies/mL [ 35 ], and only 29% achieved 6-month viral suppression to < 50 copies/mL among infants starting ART < 3 months of age in a cohort in Cape Town [ 36 ]. In contrast, 71% of infants in the EIT study had HIV-1 RNA < 40 copies/mL at the 24-week visit.…”
Section: Discussionmentioning
confidence: 97%